Social Media Sentiment Analysis to Understand Agricultural Market Trends and Consumer Preferences - January Rizki (Jurnal Minfo Polgan, 2023)
Social media has become a very important communication platform in the daily life of modern society. People use these platforms to share their experiences, opinions, and preferences regarding various topics, including agricultural and food products. This research aims to conduct social media sentiment analysis to understand agricultural market trends and consumer preferences. This research is a literature review that adopts a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that social media sentiment analysis is an invaluable tool for agricultural industry players in understanding market trends and consumer preferences. Using natural language processing and machine learning techniques, this analysis enables real-time monitoring of consumer opinions and feelings regarding agricultural products and agriculture-related issues.